Computer-assisted discovery of natural inhibitors for platelet-derived growth factor alpha as novel therapeutics for thyroid cancer - Khalid, Hira; Sattar, Farah; Ahmad, Iqra; Junior, Valdir Ferreira de Paula; Nishan, Umar; Ullah, Riaz; Dib, Hanna; Omari, Khaled W.; Shah, Mohibullah (Frontiers in Pharmacology, 2025)
Platelet-derived growth factor alpha (PDGFRA) plays a significant role in various malignant tumors. PDGFRA expression boosts thyroid cancer cell proliferation and metastasis. Radiorefractory thyroid cancer is poorly differentiated, very aggressive, and resistant to radioiodine therapy. Thus, novel anticancer drugs that inhibit its metastasis are urgently required. In this context, we proposed the PDGFRA inhibitors by an optimized structure-based drug design approach. We performed a virtual screening of metabolites derived from anticancer medicinal plants (Swertia chirayita, Myristica fragrans, and Datura metel) and successfully identified seven hits, namely cis-Grossamide K, Daturafoliside O, N-cis-feruloyltyramine, Maceneolignan H, Erythro-2-(4-allyl-2, 6-dimethoxyphenoxy)-1-(3, 4, 5-trimethoxyphenyl) propan-1, 3-diol, Myrifralignan C, and stigmasteryl-3-O-β-glucoside as potential PDGFRA inhibitors. Not only the top 7 hits exhibited higher docking scores in docking simulation but also optimal drug-likeness and non-toxic profiles in pharmacokinetics analysis among 119 compounds. Our top hits are non-mutagenic, can cross the blood-brain barrier, and inhibit p-glycoprotein, while the N-cis-feruloyltyramine has the potential to become a lead compound. The protein-ligand stability of the top 3 hits, namely cis-Grossamide K, Daturafoliside O, and N-cis-feruloyltyramine, and their interactions at the potential binding site of target protein were confirmed through molecular dynamic simulations. We also analyzed pharmacophoric features for stable binding in the PDGFRA active site. These drug candidates were further characterized to predict their biological activity spectra in the human body and medicinal characteristics to know their extensive behavior in laboratory testing. This study necessitates the in-vitro and in-vivo studies to confirm the potential of our hits for the discovery of novel therapeutics against the thyroid cancer.